Survei Sarana dan Prasarana Pendidikan Jasmani Di SMP Negeri Se-Kecamatan Bungkal Kabupaten Ponorogo - Wibawa Hs, Bima Satria; Warthadi, Anugrah Nur; Nurhidayat , Nurhidayat (Jurnal Porkes, 2024)
The purpose of this study was to assess the quality of facilities and infrastructure in State Junior High Schools in Bungkal District, Ponorogo Regency. This research uses quantitative descriptive research. The population was 2 schools and the sample was 2 schools. The data collection techniques used were observation, interview and documentation. The data analysis used was descriptive quantitative by classifying the type of data obtained from the observation sheet. Data is categorized regarding the number of existence, condition, ownership status of physical education infrastructure facilities with a clarification formula. The results of the data description that has been described by the researcher, the mean is 4.05 while for Standard Deviation is 2.7, included in the very high category because it has a value above 8.115. There are several physical education facilities and infrastructure that are in damaged or unfit for use. In addition, there are a minimal number of physical education facilities and infrastructure. It can be concluded that the facilities and infrastructure have a high category, it's just that there are still some physical education equipment that is still lacking in number and some are not complete, such as jumping chests, hoops, soccer fields and bracelets.